Challenges to implementation of artemisinin combination therapy policy in Uganda - Batwala, Vincent; Magnussen, Pascal; Nuwaha, Fred (My University, 2010)
Uganda launched an artemisinin combination therapy (ACT) policy in 2006, using artemether-lumefantrine (AL) as first-line treatment for uncomplicated malaria, but insufficient information is available regarding its implementation. Semi-structured interviews were conducted with key personnel: 32 clinical and four laboratory staff from 32 health centres (HCs) in Bushenyi and Iganga districts and the Ministry of Health. Structured interviews with 613 patients receiving malaria treatment at six randomly chosen HCs were held. Data were collected on availability of antimalarials, treatment guidelines, staffing and malaria treatment decisions. Posts for clinical staff were inadequately filled. Only 15 (46.9%) HCs stocked AL for all weight categories. Nationwide, AL was out-of-stock March–July 2007. Twenty-one (65.6%) HCs stocked chloroquine. Out of 193 patients, 177 (91.7%) used antimalarials other than AL before coming to HCs. The unrecommended antimalarials were mainly sourced from the private for profit (PFP) sector yet there were no guidelines regarding provision of AL in the PFP sector. Only 53/613 (8.6%) patients were examined for parasites and only 8 (15.1%) had a positive blood slide. The majority of the patients attending HCs (560; 91.4%) received antimalarials but only 323 (57.7%) received AL. In order to improve the implementation of the current policy, AL should be availed in adequate amounts at all points of care including the PFP sector; non-recommended drugs should be withdrawn from the market and it should be ensured that malaria is confirmed by laboratory diagnosis. Study registration: Clinicaltrials.gov NCT00565071.
Keywords: Artemisinin Combination Therapy, Malaria diagnosis, Treatment Topic: chloroquineantimalarialscombined modality therapymalariaparasitespersonnel staffing and schedulinghuman placental lactogenugandaguidelinesartemisininelaboratory diagnosistreatment guidelinesartemether/lumefantrine